2013
DOI: 10.4239/wjd.v4.i6.295
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials on corticosteroids for diabetic macular edema

Abstract: Diabetic macular edema (DME) is a common cause of visual impairment in diabetic patients. It is caused by an increase in the permeability of the perifoveal capillaries and a disruption of the blood retinal-barrier. The pathogenesis of DME is multifactorial. Several therapeutic modalities have been proposed for the treatment of DME. Corticosteroid treatments have emerged as an alternative therapy for persistent DME or refractory to conventional laser photocoagulation and other modalities, due to anti-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 78 publications
(105 reference statements)
0
19
1
4
Order By: Relevance
“…Thus, the gold standard treatment for DME is no longer laser photocoagulation [5,6] but new therapies targeting the inflammatory components of DME, including intravitreal anti-VEGF agents [7,8] and corticosteroids [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the gold standard treatment for DME is no longer laser photocoagulation [5,6] but new therapies targeting the inflammatory components of DME, including intravitreal anti-VEGF agents [7,8] and corticosteroids [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite the concerns of cataract and glaucoma with corticosteroid therapies, these agents have been extensively used in ophthalmological practice through systemic, topical, periocular and intravitreal routes [38,39]. With increasing focus on improved visual outcome in patients with ME, there has been a change in the pattern of drug delivery designing.…”
Section: Expert Opinionmentioning
confidence: 99%
“…10 Intravitreal injections of triamcinolone acetonide (TA) have become increasingly popular for treating a broad spectrum of retinal diseases, 11 such as diffuse DME, 12,13 exudative age-related macular degeneration, [14][15][16] uveitis, 17 and macular edema from central retinal vein occlusion. 18,19 Some recent placebo-controlled trials conducted in patients with DME have indicated that intravitreal injections of TA are effective in improving visual acuity (VA) and reducing central macular thickness (CMT), both in early [20][21][22] and late follow-up visits.…”
Section: Introductionmentioning
confidence: 99%